Multiphase-flow numerical modeling of the 18 May 1980 lateral blast at Mount St. Helens, USA - Widiwijayanti, Christina. (2012)
Volcanic lateral blasts are among the most spectacular and devastating of natural phenomena, but their dynamics are still poorly understood. Here we investigate the best documented and most controversial blast at Mount St. Helens (Washington State, United States), on 18 May 1980. By means of three-dimensional multiphase numerical simulations we demonstrate that the blast front propagation, final runout, and damage can be explained by the emplacement of an unsteady, stratified pyroclastic density current, controlled by gravity and terrain morphology. Such an interpretation is quantitatively supported by large-scale observations at Mount St. Helens and will influence the definition and predictive mapping of hazards on blast-dangerous volcanoes worldwide.